Dietitians' perceptions and experience of blenderised feeds for paediatric tube-feeding. Issue 2 (27th September 2016) - Armstrong, Janis; Buchanan, Elaine; Duncan, Hazel; Ross, Kathleen; Gerasimidis, Konstantinos
Abstract : Objective: There is an emerging interest in the use of blenderised food for tube-feeding (BFTF). This survey explored paediatric dietitians' perceptions and experiences of BFTF use. Design: A web-based questionnaire was distributed to the Paediatric group of the British Dietetic Association. The survey captured dietitians' personal opinions and experience supporting children on BFTF, and the perceptions of carers. Results: Of the 77 respondents, 19 were aware of professional guidelines and 63 had never received training on BFTF. Thirty-four would not recommend BFTF and 11 would advise against its use; yet 43 would recommend it to supplement commercial feeds. Fifty-seven would change their perception about BFTF if there were evidence-based guidelines. Forty-four would feel confident to support a patient using BFTF. Forty-three had previous experience supporting a patient with BFTF. The main concerns perceived by dietitians, pertinent to the use of BFTF, were nutritional inadequacy (n=71), tube blockages (n=64) and increased infection risk (n=59) but these were significantly higher than those experienced by themselves in clinical practice (p<0.001 for all three). A reduction in reflux and vomiting and increased carer involvement were the main perceived and observed benefits by both dietitians and carers. Conclusions: The use of these feeds for tube-fed children is increasingly being seen as a viable choice. Dietitians experienced significantly fewer issues with the use of BFTF in clinical practice compared with their self-reported apprehensions in the survey. Well-controlled studies are now needed to objectively assess the benefits, risks, costs and practicality of BFTF.